Implementation of the Use of Ubay Animation Media in Fiqh Learning in Grade 1 SDIT Exemplary Imam Syafi'i, Tanjung District, North Lombok Regency for the 2023/2024 Academic Year - Pramudita, Gia Alfina; Habiburrahman, H. Lalu; Jannah, Rauhun (Lembaga Bale Literasi, 2024)
Abstract Gia Alfina Pramudita (2024). This research aims to determine the implementation and impact of using Ubay animation media on learning Islamic jurisprudence and prayer material in class 1 of SDIT Teladan Imam Syafi'i. This research was carried out at SDIT Teladan Imam Syafi'I, Tanjung District, North Lombok Regency. The subjects in this research consisted of grade 1 teachers, school principals and grade 1 students. This research method used a qualitative case study type method with data collection techniques using observation, interviews, documentation and questionnaires. The results of the research are that the implementation of the use of Ubay Animation media in Fiqh lessons in class 1 of SDIT Teladan Imam Syafi'i has been carried out in accordance with the stages of the learning process while still paying attention to the condition of the students so that the learning process becomes more enjoyable. And with this research, it can be seen that the impact of implementing the use of Ubay animation media can make the learning process more enjoyable, make it easier for students to understand the material and can focus students on the prayer fiqh learning material. Keywords:Prayer Fiqh Learning, Learning Media, Ubay Animation.